The difficult doctrine of the love of God - Carson, Don A.; W.H. Griffith Thomas Lectures, Dallas Theological Seminary, February, 1998. (Leicester, UK IVP, 2000)
Includes bibliographical references and index.
Originally prepared as the W.H. Griffith Thomas Lectures, Dallas Theological Seminary, Feb, 1998. Also delivered, each time slightly revised, at Carey Baptist College, NZ, Moore Theological College, Sydney, Aust., and at Gilcomston Church, Aberdeen, Scotland.
Keywords: God -- love